Enhancing Narrative Writing Skills through Cooperative Learning and Sequential Image Media in Islamic School - Zahro, Amalia; Hadiyan Wijaksana, Haris; Nur Qorimah, Esti; Setiawan, Budi; Safrizal, Safrizal; Islahuddin, Islahuddin (International Journal of Elementary School, 2025)
One of the main challenges in learning Indonesian is students' difficulty in expressing ideas, opinions, thoughts, or feelings in written form. These difficulties include selecting appropriate words, constructing sentences, determining a theme or topic, and developing a writing framework. This study aims to improve narrative essay writing skills through the implementation of the Cooperative Learning model with sequential image media. The research was conducted as Classroom Action Research in Islamic school, with the research subjects being fourth-grade students. Data collection techniques included observation, tests, and documentation. The collected data were analyzed using qualitative and quantitative descriptive analysis techniques. The results indicate that implementing the Cooperative Learning model and sequential image media significantly contributes to enhancing students' writing skills. In the pre-cycle stage, the percentage of students achieving learning mastery was 40%, which increased to 60% in the first cycle and reached 87% in the second cycle.